Metacognition: Foundation of Cognitive Efficiency in the learning of English by Learners in the Final Year Classes of secondary school in Foumban- Cameroon - Ngam, Mounchili Divine; Rosaline, Tcheundjio (Journal of Innovation in Education and Social Research, 2025)
In this scientific article which highlights the basis of metacognition on efficiency in learning English. It is clear to see that metacognition is an essential lever in any learning process, as it enables the learner to measure his or her strengths and weaknesses in relation to the task to be solved, to know the characteristics of the task and finally to make the right choice of strategies to adopt when carrying out a task. Metacognitive activity therefore presupposes that the subject is capable of reflecting on and acting on his or her cognitive processes. In addition, Doly (1997) distinguishes two components of metacognition: knowledge about cognition called ‘metacognition’ and control skills called ‘metacognitive skills’. It is now clear that a metacognitive subject knows how to ask questions about his or her own knowledge in order to optimise his or her chances of success when faced with a given task, because he or she has knowledge about himself or herself, about the task to be performed and about the strategies to be used to perform the task. Unsuccessful learners are not metacognitive, whereas successful learners are metacognitive, transferring, self-regulating and autonomous. This is what illustrates the value of metacognition in the teaching and learning process, which we will present throughout this article.